Hubungan Siklus Menstruasi, Konsumsi Tablet Tambah Darah (TTD) Dan Asupan Vitamin C Dengan Status Anemia Pada Siswi SMAN 27 Jakarta - Jesika Agustia; Waisaktini Margareth; Rosmida Magdalena Marbun (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
The prevalence of anemia in adolescents in Indonesia is 32%, where women are more anemic by 27.2% and men by 20.3%. In DKI Jakarta, 23% of female adolescents experience anemia. This study aims to analyze the relationship between the menstrual cycle, consumption of Blood Supplement Tablets (TTD) and intake of vitamin C with anemia status in female students of SMAN 27 Jakarta. The study design was cross sectional with 78 female respondents. The data collected included menstrual cycle data, consumption of Blood Supplementary Tablets (TTD) and intake of vitamin C obtained by interview using a questionnaire. Data processing used the chi-square test for menstrual cycle variables and vitamin C intake. Meanwhile, Fisher's test was used for the consumption of blood supplement tablets (TTD) variables. The results showed that 24.4% (19 female students) had anemia, 42.3% (33 female students) had abnormal menstrual cycles, 79.5% (62 female students) consumed blood supplement tablets (TTD) and intake of vitamin C was classified as insufficient by 50% (39 female students). There is a significant relationship between consumption of blood supplement tablets (TTD) and intake of vitamin C with anemia status in female students of SMAN 27 Jakarta (p-value <0.05). There was no significant relationship between the menstrual cycle and anemia status in female students at SMAN 27 Jakarta (p-value=0.984) (p>0.05).